2021
DOI: 10.1177/0363546521997101
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Revision and Reoperation Risks After Meniscectomy at the Time of Anterior Cruciate Ligament Reconstruction

Abstract: Background: An intact meniscus is considered a secondary stabilizer of the knee after anterior cruciate ligament reconstruction (ACLR). While loss of the meniscus can increase forces on the anterior cruciate ligament graft after reconstruction, it is unclear whether this increased loading affects the success of the graft after ACLR. Purpose: To identify the risk of subsequent knee surgery when meniscectomy, either partial or total, is performed at the time of index ACLR. Study Design: Cohort study; Level of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In a recent large study from Kaiser Permanente with 12 years of follow-up, meniscectomy did not influence revision rates. 32 Vindfeld et al 31 conducted a matched case-control study of 100 patients undergoing revision ACL surgery and 100 matched controls who were not revised at 11-year follow-up. Like us, those investigators found that patients who did not undergo revision were more likely to have had a meniscal tear identified during the primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large study from Kaiser Permanente with 12 years of follow-up, meniscectomy did not influence revision rates. 32 Vindfeld et al 31 conducted a matched case-control study of 100 patients undergoing revision ACL surgery and 100 matched controls who were not revised at 11-year follow-up. Like us, those investigators found that patients who did not undergo revision were more likely to have had a meniscal tear identified during the primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Meniscal Surgery. Seven studies 24,26,41,69,105,119,164 investigated the association of concomitant meniscal surgery with revision or rerupture after ACLR. The metaanalysis showed that there was a nonsignificant effect of meniscal surgery on the odds of revision or rerupture (OR, 1.19; 95% CI, 0.77-1.84; P = .44; I 2 = 88%) (Figure 4).…”
Section: Femoralmentioning
confidence: 99%
“…Additionally, a recent study from the NZACL investigated the effect of suspensory versus tibial fixation devices on revision rates following ACL-R. Moreover, data from Kaiser Permanente's ACLR registry was recently used to identify differences in revision risk with respect to the timing of ACL-R [36] and concomitant meniscus surgery [37]. Importantly, data collection from non-operatively treated patients with ACL injury enables the comparison of outcomes following operative and non-operative treatment approaches [38,39].…”
Section: Comparative Studiesmentioning
confidence: 99%